Purificação e concentração do extrato de Stevia Rebaudiana Bertoni através de membranas microporosas - Moreschi, Silvânia Regina Mendes (1999)
In this work it was investigated the use of membrane separation processes, ultrafiltration (UF) and diafiltration (DF), to purify and concentrate extract of Stevia Rebaudiana Bertoni leaves. Experiments were carried out in a cross-flow filtration equipment under ambient temperature. It was used three different membrane cut-offs: 10,000 Daltons (cellulose acetate), 30,000 Daltons (polysulphone) and 100,000 Daltons (polysulphone). The first and the second membranes were tested under 8, 10 and 12 Psi inlet pressure and that of 100,000 Daltons was tested under 8 Psi inlet pressure. The following parameters were evaluated: permeate flux, purity and percentage of colour and turbidity removals of crude extract, permeate and retentate. Initial values of permeate flux were proportional to the membrane aperture (cut-off). The 10,000 Daltons cut-off membrane presented a more stable flux along the filtration time than the two other membranes. The best results of purity and effective turbidity removals were obtained with the membrane of 30.000 Daltons under 10 Psi, while best results of colour removal were obtained with 10,000 Daltons membrane under 8 Psi. Diafiltration was carried out with the 30,000 Daltons membrane under 10 Psi. This have made it possible to increase the purity from 34% (in the Ultrafiltration) to values around 55%.